2010
DOI: 10.1111/j.1540-6237.2010.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cultural Assimilation of Mexican Americans: How Rapidly Do Their Gender-Role Attitudes Converge to the U.S. Mainstream?*

Abstract: Objective. This study assesses the pace of cultural assimilation of Mexican Americans by comparing changes in their gender-role attitudes over generations to the European-origin U.S. mainstream. Methods. Using cumulative data from the 1972-2004 General Social Survey, we examine the rate at which progressive generations of Mexican Americans approach the mainstream gender-role attitudes. We also employ a set of logistic regressions to assess the differences in gender-role attitudes between Mexican and European A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Third, respondents who interviewed in Spanish (versus in English) strongly endorsed more traditional gender ideologies, a finding consistent with literature linking cultural assimilation with gender traditionalism. Overall, this pattern is broadly consistent with previous studies highlighting the role of factors such as SES, generation, and acculturation with Latina/o gender and family patterns (e.g., (Raley et al 2004;Su et al 2010)). Few other variables emerged as significant predictors of gender ideology among this sample of Latinas/os.…”
Section: Estimated Net Effects Of Covariatessupporting
confidence: 81%
See 1 more Smart Citation
“…Third, respondents who interviewed in Spanish (versus in English) strongly endorsed more traditional gender ideologies, a finding consistent with literature linking cultural assimilation with gender traditionalism. Overall, this pattern is broadly consistent with previous studies highlighting the role of factors such as SES, generation, and acculturation with Latina/o gender and family patterns (e.g., (Raley et al 2004;Su et al 2010)). Few other variables emerged as significant predictors of gender ideology among this sample of Latinas/os.…”
Section: Estimated Net Effects Of Covariatessupporting
confidence: 81%
“…Much of the scholarly attention in this area has centered on (a) indicators of acculturation such as generation, length of time in the United States, and language spoken at home and (b) structural factors such as education, income, and employment status. Briefly, the available evidence indicates that U.S. born Latinas/os or Latina/o immigrants who have spent significant time in the country tend to hold more egalitarian and less traditional gender ideologies than others (Parrado and Flippen 2005;Su et al 2010). Indicators of acculturation such as speaking English (versus Spanish) at home have also been associated with more egalitarian gender ideologies (Kane 2000;Vasquez-Nuttall et al 1987).…”
Section: Latina/o Gender Ideology: Integrating Current Research With mentioning
confidence: 99%
“…Thus, it may be acculturative stress is related to redefining marital expectations and gender roles while attempting to maintain tradition. As beliefs, actions, social pressures and expectations may not align in acculturated individuals and differ across generations (Su et al, 2010), this conflict could be contributing to psychological distress in Mexican-American mothers. On the other hand, the Anglo value of material success refers to prioritizing of earning money or measurable success in terms of goods.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study of Mexican immigrant non-skilled workers found low levels of work-family conflict overall, but higher levels in women than in men (Grzywacz et al, 2007). Family and gender-role patterns in Mexican households are affected by many factors including national origins, immigration experiences, and generation (Landale et al, 2006; Parrado & Flippen, 2005; Su et al, 2010). Nonetheless, Latinas—particularly those of higher SES—may be challenged by dual home and work experiences relative to their male counterparts, and this may help explain their increased chronic stress, especially in the areas of caregiving and work, in the current study.…”
Section: Discussionmentioning
confidence: 99%